Recent Progress in Waveguide-Integrated Graphene Photonic Devices for Sensing and Communication Applications - Wang, Jiaqi; Xing, Zhengkun; Chen, Xia; Cheng, Zhenzhou; Li, Xuejin; Liu, Tiegen (Frontiers in Physics, 2020)
Graphene is a two-dimensional material with numerous intriguing optical properties, such that graphene photonic devices have attracted great interest for sensing and communication applications. However, surface-illuminated graphene photonic devices usually suffer from weak light-matter interactions due to the atomic-layer thickness of graphene, seriously limiting the performances of such devices. To tackle this problem, waveguide-integrated graphene photonic devices have been demonstrated since 2010, which offer the advantage of much longer interaction length between the evanescent field of the optical waveguide and graphene than the surface-illuminated devices. Moreover, the fabrication of waveguide-integrated graphene photonic devices is compatible with the CMOS technology, allowing potentially low-cost and high-density on-chip integration. To date, a tremendous interest is growing in the hybrid integration platform composed of graphene and silicon photonic integrated circuits. In this paper, we review the recent progress in waveguide-integrated graphene photonic devices and their applications in sensing and communication.